Determination of stress, depression and burnout levels of front‐line nurses during the COVID‐19 pandemic - Murat, Merve; Köse, Selmin; Savaşer, Sevim (International journal of mental health nursing, 2021)
All healthcare professionals, especially nurses, are affected psychosocially due to reasons such as uncertainty and work intensity experienced during the COVID‐19 pandemic. In this descriptive study, it was aimed to determine the stress, depression and burnout levels of front‐line nurses. Data were obtained from 705 nurses who worked at hospitals during the COVID‐19 pandemic between May and July 2020, using a Personal Information Form, the Perceived Stress Scale, Beck Depression Inventory and Maslach Burnout Inventory. The data collection tools were sent online to nurse managers, requesting front‐line nurses to answer the forms and scales. The nurses were mostly women and had bachelor’s degrees, single and worked as nurses for between 1 and 10 years. They had high levels of stress and burnout and moderate depression. Those who were younger and had fewer years of work experience felt inadequate about nursing care and had higher levels of stress and burnout. More burnout was detected in nurses who had a positive COVID‐19 test and did not want to work voluntarily during the pandemic. The authors suggest that preventive and promotive interventions in mental health should be planned and implemented to improve the mental health and maintain the well‐being of front‐line nurses during the pandemic, and to prepare nurses who may work during pandemics in the future.